2018
DOI: 10.1002/hep.29529
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐infiltrating PD‐L1hi cross‐dressed dendritic cells regulate antidonor T cell responses in mouse liver transplant tolerance

Abstract: These findings suggest that graft-infiltrating PD-L1 CD-DCs may play a key role in the regulation of alloimmunity and in the induction of liver transplant tolerance. (Hepatology 2018;67:1499-1515).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
89
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 52 publications
5
89
0
2
Order By: Relevance
“…Liver‐resident antigen (Ag)–presenting cells (APCs) of hematopoietic and nonhematopoietic origin, which have been shown to regulate inflammatory and T cell–mediated immune responses, include dendritic cells (DCs), Kupffer cells, sinusoid‐lining endothelial cells, and hepatic stellate cells. In particular, liver DCs, which are regarded as critical instigators and regulators of innate and immune‐mediated inflammatory responses, have been implicated in control of acute liver injury, T cell–mediated and autoimmune hepatitis, and the promotion of oral and transplant tolerance.…”
mentioning
confidence: 99%
“…Liver‐resident antigen (Ag)–presenting cells (APCs) of hematopoietic and nonhematopoietic origin, which have been shown to regulate inflammatory and T cell–mediated immune responses, include dendritic cells (DCs), Kupffer cells, sinusoid‐lining endothelial cells, and hepatic stellate cells. In particular, liver DCs, which are regarded as critical instigators and regulators of innate and immune‐mediated inflammatory responses, have been implicated in control of acute liver injury, T cell–mediated and autoimmune hepatitis, and the promotion of oral and transplant tolerance.…”
mentioning
confidence: 99%
“…In mice, these allografts are often accepted without requirement for immunosuppressive therapy (61). The immune privilege status of the liver is associated with the presence of resident professional and nonprofessional APCs, including DCs and hepatic macrophages (Kupffer cells) (6264), liver sinusoidal endothelial cells (LSEC) (65), hepatic stellate cells (66), and hepatocytes (67). Liver DCs are characterized by their immaturity (68, 69) and tolerogenic properties (7072).…”
Section: Immune Privileged Sites and Transplantsmentioning
confidence: 99%
“…A recent study from Thomson’s laboratory supported the role of antigen cross-dressing in mouse spontaneous liver transplant tolerance. They reported that the majority of recipient DCs found in accepted liver allografts were cross- dressed with donor MHC class I expressing high levels of PD-L1 and IL-10 as compared with non–cross-dressed-DCs isolated from the graft (64). Concurrently, graft- infiltrating T cells displayed PD-1 and TIM-3, which are features of exhausted cells, on their cell surface (64).…”
Section: Immune Privileged Sites and Transplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, they have used CD11c‐diphtheria toxin receptor donors to document that myeloid DCs are essential for liver tolerance induction. The current work in this issue of H epatology not only extends in‐depth exploration of the tolerogenic mechanisms of hepatic DCs but also illuminates a new aspect in transplant immunology, i.e., cross‐dressing in recipients' APCs.…”
mentioning
confidence: 99%